PENGGUNAAN BAHAN FINISHING PADA ROTAN NON KOMERSIAL SEBAGAI BAHAN KERAJINAN - Hamdi, Saibatul; Arhamsyah, Arhamsyah (Kementerian Perindustrian, 2011)
Development of the rattan furniture industry today is quite fast although the amount of raw materials are decreasing, especially in commersial rattan commodities such as Manau,Â Irit, Taman, Sega, etc. Their price is quite expensive too five species of rattan were used as research materials. There are Manau (Calamus mettanensis Becc), Toho (Calamus sp), Galang (Daemonorops verticilaris Griff Mart), Hijau (Calamus sp) and simpurut (Calamus panajuga Becc). For finishing materials, clear glass melamine (ML 131 and NC 141) were used in this research with three different immersion timer for 24 hours, 36 hours and 48 hours long. An immersion method without using any finishing materials was done as control materials. Result show that the average of volume expansion of rattan speseis using NC 141 are 1,56-3,16% in Marau; 1,36-2,91%; in Toho; 2,01-3,05% in Galang; 2,12-3,20% in Hijau and 1,90-2,14 in Simpurut. In the other hand, the average of volume expansion of rattan species using melamin ML 131 are 1,27-2,58% in Marau; 1,46-2,51% in Toho; 2,30-3,23% in galang; 1,10-2,79% in Hijau and 1,45-2,55% in Simpurut. In control materials the average of expantion volume in 5 species rattans is 2,53-3,99%. From those results, the best method was shown in using NC 141 which can prevent the volume expansion and give great influence in volume expansion value.Keywords: rattan, finishing material, melamine ML 131, melamine NC 141, volume expantion.